Traditional prenatal and postpartum food restrictions among women in northern Lao PDR - Taryn J. Smith; Xiuping Tan; Charles D. Arnold; Dalaphone Sitthideth; Sengchanh Kounnavong; Sonja Y. Hess (Wiley, 2022)
Abstract Culturally determined food restrictions are common among pregnant and postpartum women in Asia. This study aimed to describe perinatal dietary restrictions, factors associated with food avoidances and attainment of minimum dietary diversity (MDD‐W) among women in Lao PDR. Mother-child (aged 21 days to <18 months) dyads (n = 682) were enrolled into a cohort study in northern Lao PDR and interviewed at one time point postpartum. During pregnancy and postpartum, 1.6% and 97% of women reported following dietary restrictions, respectively. Cluster analysis identified four distinct postpartum dietary patterns: most restrictive (throughout first 2 months postpartum); least restrictive; 2 weeks highly restrictive and 1 month highly restrictive, followed by 19%, 15%, 5% and 62% of women, respectively. Greater maternal age, gravidity and higher household socioeconomic status were associated with allowing more diverse foods, while women from food insecure households followed more restrictive diets for longer. Women belonging to the Hmong ethnic group followed a highly restrictive diet of white rice and chicken for the first month postpartum. MDD‐W was achieved by 10% of women restricting their diet at the time of the interview compared with 17% of women who were consuming their normal diet (p = 0.04). Postpartum dietary restrictions are widespread among women in northern Lao PDR. These highly restrictive diets, low dietary diversity and food insecurity likely contribute to micronutrient deficiencies in women that may have important consequences for their breastfed infants through reduced breastmilk micronutrient content, which requires further exploration. Culturally appropriate strategies to increase micronutrient intakes among women should be considered.